Cities and the mongol conquest: urban change in Central Asia 1200-1400 - Campbell, K (2021)
In the early decades of the 13th century, the Mongols swept through Central Asia, sacking the cities of the Khwarazmian Empire and apparently causing economic chaos throughout the region. The Persian historians Rashid al-din, Juvaini and others describe this as a traumatic event with cities razed and populations slaughtered. This thesis archaeologically examines urban change from the 12th to 14th centuries at three cities impacted by the conquest: Otrar in Kazakhstan, Barda in Azerbaijan and Merv in Turkmenistan. Following excavation, re-excavation and review of available published and unpublished material, no convincing evidence of Mongol destruction or victims of the described slaughter were found at any of the sites. At Merv, the only site to witness a negative impact of the conquest according to the archaeological evidence, the picture is one of depopulation and desertion rather than destruction. As such the ‘destruction’ caused by the Mongols at this site (and others) might be seen as Mongol-inflicted depopulation through conscription and enslavement, leading to the decay of the mudbrick city rather than outright destruction. At Otrar, previous excavations had reported a decades long abandonment on the city’s shahristan, but radiocarbon dating and contextualisation with ceramic and coin evidence showed that this district of the city was abandoned by at least 1150, almost a century before the arrival of the Mongols in 1219. Indeed, broader coin finds across the main part of Otrar show that the city may have been effectively abandoned or at least significantly depopulated through the 12th and early 13th centuries.